F. Méhul: Membre de l'Institut - Wintter, Heinrich Eduard von, 1788-1829 (artist):::Creator:::::::::::: (Leipzig; Germany; Chez Breitkopf & Härtel)
Reprint of engraving of Etienne-Nicholas Méhul by Heinrich Wintter.